Mothers at Risk: Factors Affecting Maternal Postpartum Length of Stay. Issue 4 (October 2018) - Van Otterloo, Lucy; Connelly, Cynthia; Gould, Jeffrey; Abreo, Anisha; Main, Elliott
Abstract : Perinatal complications linked to maternal comorbidities contribute to increased healthcare utilization through an extended postpartum length of stay (LOS). Understanding factors influencing postpartum LOS may minimize the adverse effects associated with comorbidities and complications. The purpose of this study was to identify risk factors with the greatest odds of increasing postpartum LOS. Linked 2008-2009 hospital discharge and birth certificate data were used to examine comorbidities and complication codes in 1 015 424 births. The overall rate for an extended LOS (vaginal: >5 days/cesarean: >6 days) was 3.63 per 1000 live births. Complications were present in 17% of pregnancies; multiple complications were seen in 1%. Chronic hypertension was associated with an extended stay for both vaginal and cesarean births (odds ratio [OR] = 5.89 [95% CI, 4.39-7.88]; OR = 3.57 [95% CI, 3.05-4.17], respectively). Puerperal infections (OR = 6.86 [95% CI, 5.73-8.21]), eclampsia (OR = 17.07 [95% CI, 13.76-21.17]), and transfusions (OR = 11.66 [95% CI, 9.20-14.75]) occurred most frequently and conferred the highest odds of an extended stay for vaginal births. Cerebrovascular conditions (OR = 15.32 [95% CI, 11.90-19.60]) and infection (OR = 15.35 [95% CI, 10.11-23.32]) conferred the highest odds of an extended LOS for cesarean births. The earlier risk factors are recognized, the sooner processes can be initiated to optimize organizational preparation, thus decreasing adverse maternal outcomes and extended hospital stays.